The Effect Use of Different Binding Materials on Water Holding Capacity, Water Content and Crude Fiber Content of Chicken Nuggets - Alfonsus Liquori Taus; Paulus Klau Tahuk; Kristoforus W Kia (Journal of Tropical Animal Science and Technology, 2022)
This study aims to determine the water holding capacity, moisture content and crude fiber content of chicken nuggets made using different types of flour as a binder. This research was conducted at the Laboratory of the Faculty of Animal Husbandry, Nusa Cendana University, Kupang for 1 week. The method used in this study was a completely randomized design (CRD) with 3 treatments and 3 replications. The treatments were P1 (making nuggets with porang flour), P2 (making nuggets with tapioca flour), and P3 (making nuggets with wheat flour). The variables observed in this study included water holding capacity, water content and crude fiber content. The data obtained were analyzed using the Anova test and Duncan's test. The results of the study showed that the water holding capacity of chicken nuggets P1, P2, P3 were 36.956%, 34.621%, 32.756%, respectively. The water content of chicken nuggets was 64.17%, 59.95%, 57.71%, respectively. The crude fiber content of chicken nuggets is 1.387%, 1.169%, and 0.638% respectively. The statistical analysis showed that the treatment had a significant effect on the water holding capacity of chicken nuggets, water content of chicken nuggets and crude fiber content of chicken nuggets (P<0.05). It was concluded that the water content of chicken nuggets made from wheat flour and tapioca was in accordance with SNI, while the production of nuggets made from porang flour exceeded the Indonesian National Standard, but porang flour had the advantage of being able to bind water better.